2003
DOI: 10.1351/pac200375040435
|View full text |Cite
|
Sign up to set email alerts
|

Carbenes. Pincers, chelates, and abnormal binding modes

Abstract: Routes to pincer and chelate carbene complexes of Pd, Rh, and Ir include double geminal CH activation, metallation, and CH activation. Abnormal binding via imidazole C5 can occur, and ion pairing can strongly influence C2 vs. C5 binding. Prior ligand binding via pyridine N before metallation is not essential. Computational methods are used extensively, for example, to compare N vs. C binding in imidazole. The possibility of C binding by histidine in metalloenzymes is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 10 publications
3
28
0
Order By: Relevance
“…Accordingly, the five-membered ring features structural parameters that are typical for complexes containing abnormal carbene ligands of the imidazolium-4-yl type. [16] The BÀC2 distance is 1.649 (3) and is almost identical to that found in the normal adduct between tris(pentafluorophenyl)borane and the sterically less-encumbered carbene 1,3,4,5-tetramethylimidazolin-2-ylidene. [15] The tert-butyl group at N1 is interlocked with two C 6 F 5 rings, suggesting that the rotation around the B À C axis might be severely hindered.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Accordingly, the five-membered ring features structural parameters that are typical for complexes containing abnormal carbene ligands of the imidazolium-4-yl type. [16] The BÀC2 distance is 1.649 (3) and is almost identical to that found in the normal adduct between tris(pentafluorophenyl)borane and the sterically less-encumbered carbene 1,3,4,5-tetramethylimidazolin-2-ylidene. [15] The tert-butyl group at N1 is interlocked with two C 6 F 5 rings, suggesting that the rotation around the B À C axis might be severely hindered.…”
supporting
confidence: 60%
“…Recrystallization from CHCl 3 /pentane solution afforded single crystals suitable for an X-ray diffraction analysis, [20] and the molecular structure reveals the formation of the adduct 4, which contains an "abnormal" carbene ligand ( Figure 3). [16] The B(C 6 F 5 ) 3 moiety is attached to the 4 position of the imidazole heterocycle, which involves migration of the corresponding hydrogen atom to the former carbene carbon atom. Accordingly, the five-membered ring features structural parameters that are typical for complexes containing abnormal carbene ligands of the imidazolium-4-yl type.…”
mentioning
confidence: 99%
“…[290b] The IR spectra of complexes of type [IrCl(CO) 2 (NHC)] indicate that C 5 -metalated NHC ligands are significantly stronger electron donors than their C 2metalated analogues. [290] The specific type of donor in the donor-functionalized imodazolium salts appears to be of some importance for the course of the metalation. Peris et al [259] and Danopoulos et al [291] prepared iridium NHC complexes using pyridylfunctionalized imidazolium salts.…”
Section: Methodsmentioning
confidence: 99%
“…[288] The formation of a complex with a C 5 -metalated NHC ligand was initially surprising since DFT calculations on similar complexes had previously shown that the derivative with the C 2 -metalated NHC ligand is about 20 kcal mol À1 more stable than those with C 4 /C 5 -metalated NHC ligands. [289] Subsequent detailed studies by Crabtree et al demonstrated [290] that N-pyridyl functionalized imidazolium salts can form iridium complexes with C 2 -or C 5 -metalated NHC ligands depending on the type of N'-substituent, the counterion, and the bite-angle of the bidentate ligand (Scheme 90). When the N'-substituent is methyl and the anion bromide,…”
Section: Abnormal Carbenesmentioning
confidence: 99%
“…This may be the reason why the number of chelating NHC compounds has gradually increased over the last decade, and several reviews have appeared describing the most recent developments with regard to design, structural features and catalytic activity of complexes containing polydentate NHC ligands. [11,12,[16][17][18] Chelating Bis(NHC)s…”
Section: Chelating Nhcsmentioning
confidence: 99%